PROGRAM KEMITRAAN MASYARAKAT PENCEGAHAN STUNTING DI DESA KERTA, KECAMATAN PAYANGAN - Luh Gede Pradnyawati (Warmadewa University Press, 2022)
The problem of stunting in children under five is a very worrying problem in developing countries. This is because it is associated with the risk of decreased intellectual ability, productivity and increased risk of degenerative diseases in the future. Indonesia is one of the countries that has not been free from the problem of stunting, especially the problem of fulfilling nutrition that is still not balanced. Gianyar Regency is one of the regencies in Bali where stunting is a priority health problem. One of them is in Kerta Village, Payangan District, Gianyar Regency which is still not free from the problem of stunting. From the results of interviews with BKB cadres (Bina Keluarga Toddlers) obtained several problems related to stunting prevention programs, namely the minimal knowledge obtained by BKB cadres and the lack of knowledge of BKB cadres about stunting prevention in children in Kerta Village. The approach used is focus group discussion (FGD), conducting interactive dialogue with BKB cadres about stunting issues, as well as training and mentoring methods for BKB cadres. Discussions with BKB cadres aimed to explore all the problems regarding stunting experienced by partners. Interactive dialogue with cadres aims to provide information or counseling about the handling of stunting problems experienced by cadres. Methods of training and mentoring for BKB cadres are carried out to improve the knowledge and skills of cadres. The result of this activity is an increase in the ability of BKB cadres and they are already trained in preventing stunting problems. This training and mentoring is carried out on an ongoing basis for BKB cadres accompanied by monitoring and evaluation carried out regularly every month for cadres in Kerta Village, Payangan District, Gianyar Regency.